Partisipasi Masyarakat Dalam Pengembangan Pesantren DDI Asshirathal Mustaqim Kabupaten Pangkep - Ilham, Ilham (Al-Riwayah : Jurnal Kependidikan, 2020)
This study try to describe the participation of society in the development of Islamic Boarding School DDI Asshirathal Mustaqim in Baru Baru Tanga, Pangkep Regency, South Sulawesi. This research uses a qualitative approach. The informants of this research are community leaders, parents of students, the heads of foundations, leaders of Islamic boarding schools, the principals, the teachers, and administrative staff within the scope of Islamic boarding schools. Data was collect by using interviews, observation, and documentation techniques. The results of this study indicate that participation of society in the development of educational institutions is very active. The evidence of this argument is the society help and involved in academic and non-academic activities in building of this institutions